INDEPENDENSI AUDITOR SEBAGAI MEDIASI PENGARUH PEMAHAMAN GOOD GOVERNANCE TERHADAP KINERJA AUDITOR PADA KANTOR AKUNTAN PUBLIK DI SURAKARTA - Reza Raditya, Aris Eddy Sarwono & Dewi Saptantinah Puji Astuti (Universitas Slamet Riyadi, 2016)
The objective of the research are to analyses (1) effect understanding of good governance to auditor performance, (2) effect understanding of good governance to auditor independence, (3) effect auditor independence to auditor performance, (4) effect understanding of good governance to auditor performance, through auditor independence as the mediating variable. Population on this research are all auditors at public accountant Office in Surakarta consist of 33 respondent. Data collecting with questionnaire technique. To test the hypothesis, the researcher using the path analysis. The result reveals that (1) understanding of good governance have not significance effect to auditor performance, H1 rejected; (2) understanding of good governance have significance effect to auditor independence, H2 supported; (3) auditor independence have significance effect to auditor performance, H3 supported; (4) auditor independence is able to mediate the effect of understanding of good governance to auditor performance, H4 supported.Keywords: understanding of good governance, auditor independence, auditor performance